Effects of Processing on Cadmium Accumulation and Dietary Risk Assessment in Penaeus merguiensis from Sungsang, South Sumatra, Indonesia - Desmarinda, Jecika; Diansyah, Gusti; Putri, Wike Ayu Eka; Apri, Rezi; Nur, Muhamad (Jurnal Biologi Tropis, 2026)
Cadmium (Cd) contamination in estuarine fisheries products raises concerns due to its capacity for bioaccumulation and dietary exposure in humans. Metal accumulation in aquatic organisms is influenced by body size and tissue distribution, with higher concentrations often reported in non-muscle parts such as the head and exoskeleton. However, information on Cd distribution and consumption risk in P. merguiensis from Sungsang, South Sumatra, remains limited. This study quantified Cd concentrations in P. merguiensis stratified by size (small and large) and processing condition (peeled and unpeeled), and evaluated potential health risks using Maximum Weekly Intake (MWI) and Maximum Tolerable Intake (MTI) reference thresholds. Cadmium concentrations, determined by Atomic Absorption Spectrophotometry (AAS), ranged from 0,038 ± 0,0002 to 0,231 ± 0,0008 mg/kg. Higher levels were observed in unpeeled samples compared to peeled prawns, and larger individuals exhibited greater metal accumulation. Estimated weekly intake values for adult and child consumption scenarios remained below established tolerable limits, indicating that current exposure levels are unlikely to pose significant non-carcinogenic health risks under typical dietary patterns. Continuous monitoring is nevertheless necessary to support long-term seafood safety management in the region.